Epithelial tumours of the lacrimal gland: a clinical, histopathological, surgical and oncological survey. (4th April 2012) - von Holstein, Sarah Linéa; Coupland, Sarah E; Briscoe, Daniel; Le Tourneau, Christophe; Heegaard, Steffen
Abstract: Epithelial tumours of the lacrimal gland represent a large spectrum of lesions with similarities in clinical signs and symptoms but with different biological behaviour and prognosis. They are rare, but with aggressive malignant potential. Tumours of the lacrimal gland may present with swelling of the lacrimal gland, displacement of the eyeball, reduced eye motility and diplopia. Pain and symptoms of short duration before the first ophthalmic consultation are characteristic of malignant tumours. The histological diagnosis determines the subsequent treatment regimen and provides important clues regarding the prognosis. The purpose of this paper is to describe the various primary epithelial tumours of the lacrimal gland. In the first part of the review, the frequency, demographics, clinical presentation and diagnostic features are described. In the second part, primarily tumour‐specific histological characteristics are given. Finally, treatment modalities including surgical procedures and medical oncology as well as prognosis are discussed.